Extracellular vesicles containing the transferrin receptor as nanocarriers of apotransferrin - Mattera, Vanesa Soledad (2020)
Previous work by our group has shown the pro-differentiating effects of apotransferrin (aTf) on oligodendroglial cells in vivo and in vitro. Further studies showed the remyelinating effect of aTf in animal demyelination models such as hypoxia/ischemia, where the intranasal administration of human aTf provided brain neuroprotection and reduced white matter damage, neuronal loss, and astrogliosis in different brain regions. These data led us to search for a less invasive and controlled technique to deliver aTf to the CNS. To such end, we isolated extracellular vesicles (EVs) from human and mouse plasma and different neuron and glia conditioned media and characterized them based on their quality, quantity, identity, and structural integrity by western blot, dynamic light scattering, and scanning electron microscopy. All sources yielded highly pure vesicles whose size and structures were in keeping with previous literary evidence. Given that, remarkably, EVs from all sources analyzed contained Tf receptor 1 (TfR1) in their composition, we employed two passive cargo-loading strategies which rendered successful EV loading with aTf, specifically through binding to TfR1. These results unveil EVs as potential nanovehicles of aTf to be delivered into the CNS parenchyma, and pave the way for further studies into their possible clinical application in the treatment of demyelinating diseases.